GEOCHEMISTRY AND PETROLOGY OF TERTIARY VOLCANIC ROCKS AND RELATED ULTRAMAFIC XENOLITHS FROM THE CENTRAL AND EASTERN OMAN MOUNTAINS - Nasir S.; Al-Sayigh A.; Alharthy A.; Al-Lazki A. (My University, 2006)
The Tertiary volcanic rocks of the central and the eastern parts of the Oman Mountains consist mainly of basanites with abundant upper mantle ultramafic xenoliths. The lavas are alkaline (42-43 wt.% SiO2; 3.5-5.5 wt.% Na2O + K2O). They include primitive (11-14 wt.% MgO) features with strong OIB-like geochemical signatures. Trace element and Sr-Nd isotope data for the basanites suggest mixing of melts derived from variable degrees of melting of both garnet- and spinel lherzolite-facies mantle source. The associated xenolith suite consists mainly of spinel and Cr-bearing diopside wehrlite, lherzolite and dunite with predominantly granuloblastic textures. No significant difference in chemistry was found between the basanites and xenoliths from the central and eastern Oman Mountains, which indicate a similar mantle source. Calculated oxygen fugacity indicates equilibration of the xenoliths at - 0.43 to - 2.2 log units above the fayalite-magnetite-quartz (FMQ) buffer. Mantle xenolith equilibration temperatures range from 910-1045 + 50 °C at weakly constrained pressures between 13 and 21 kbar. Xenolith data and geophysical studies indicate that the Moho is located at a depth of ~ 40 km. A geotherm substantially hotter (90 mW m- 2) than the crust-mantle boundary (45 mW m- 2) is indicated and probably relates to tectonothermal events associated with the local and regional Tertiary magmatism. The petrogenesis of the Omani Tertiary basanites is explained by partial melting of an asthenospheric mantle protolith during an extension phase predating opening of the Gulf of Aden and plume-related alkaline volcanic rocks.
Keywords: BASANITE; EXTENSION; GEOCHEMISTRY; LITHOSPHERE; MANTLE PLUME; OMAN MOUNTAINS; P-T CONDITIONS; ULTRAMAFIC XENOLITHS